Characterization of the Avian Mitochondrial-Derived Peptide MOTS-c and Its Potential Role as a Metabolic Regulator - Xin Shu; Jiying Liu; Bingjie Xu; Hui Wang; Li Liu; Xiaotong Zheng; Jianfei Chen (Animals)
MOTS-c is a mitochondrial peptide that plays a crucial role in regulating energy metabolism, gene expression, and immune processes. However, current research primarily focuses on mammals like humans and mice, with no reports on avian MOTS-c. This study aimed to identify and characterize MOTS-c coding sequences across major poultry species through bioinformatics analysis and experimental validation. The alignment results showed high sequence similarity in the MOTS-c coding regions between avian and mammalian species. However, a single nucleotide deletion was identified in avian sequences at the position corresponding to the fourth amino acid residue of mammalian homologs, resulting in divergent downstream amino acid sequences. Despite this deletion, several residues were conserved across species. Phylogenetic analysis of mRNA sequences grouped pigeons with mammals, while protein sequence analysis revealed that poultry and mammals form separate branches, highlighting the divergence between avian and mammalian MOTS-c sequences. Tissue expression profiling demonstrated widespread distribution of chicken MOTS-c across multiple tissues, with the highest expression levels in the heart. Fasting significantly reduced heart MOTS-c expression, suggesting potential metabolic regulatory functions. Functional analysis of MOTS-c in primary hepatocytes revealed significant enrichment of the ribosome, oxidative phosphorylation, and key signaling pathways (PI3K-AKT and JAK-STAT) following 24 hours of treatment. Western blot validation confirmed MOTS-c-mediated activation of the AKT signaling pathway. This study represents the first comprehensive characterization of avian MOTS-c, providing critical insights into its evolutionary conservation and its potential functional roles in gene expression and cellular metabolism. Our findings establish a foundation for further investigation into the functions of mitochondrial-encoded peptides in avian species.